2009
DOI: 10.1016/j.jadohealth.2008.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Well-Being and Mental Health Outcomes in Adolescents With or Without Inflammatory Bowel Disease

Abstract: Purpose-The purpose of this study was to a) describe spiritual well-being (existential and religious well-being) in adolescents with inflammatory bowel disease (IBD) versus healthy peers, b) examine associations of spiritual well-being with mental health outcomes (emotional functioning and depressive symptoms), and c) assess the differential impact of existential versus religious well-being on mental health.Methods-One-hundred fifty-five adolescents ages 11-19 from a children's hospital and a university hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 32 publications
7
41
0
2
Order By: Relevance
“…Likewise, the spiritual intelligence dimensions play a significant role in predicting the quality of life of students. The findings of this research were coherent with similar studies on spiritual intelligence that is an effective factor in predicting the quality of life (Ahmad et al 2011;Bolghan-Abadi et al 2009Chamratrithirong et al 2010;Cotton et al 2009;Jafari et al 2010;Kliewer and Murrelle 2007;Moalemi et al 2010a, b;Park et al 2011;Rasic et al 2011;Shaw 2008;Wallace et al 2007). Shaw (2008) has studied the spirituality place in mental health and happiness.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Likewise, the spiritual intelligence dimensions play a significant role in predicting the quality of life of students. The findings of this research were coherent with similar studies on spiritual intelligence that is an effective factor in predicting the quality of life (Ahmad et al 2011;Bolghan-Abadi et al 2009Chamratrithirong et al 2010;Cotton et al 2009;Jafari et al 2010;Kliewer and Murrelle 2007;Moalemi et al 2010a, b;Park et al 2011;Rasic et al 2011;Shaw 2008;Wallace et al 2007). Shaw (2008) has studied the spirituality place in mental health and happiness.…”
Section: Resultssupporting
confidence: 88%
“…He noted that the spiritual activities can lead to happiness. Cotton et al (2009) in their research revealed that both healthy adolescents and others who have inflammatory bowel disease (IBD) had high levels of spiritual well-being. Having IBD moderates the relationship between spiritual well-being and mental health.…”
Section: Resultsmentioning
confidence: 99%
“…This adds support to Rasic et al (2011), further suggesting that spirituality is a protective factor from suicidal thinking. The negative association between spirituality and hopelessness suggests that individuals who have a closer perceived relationship with a higher power experience higher mental health (Cotton et al 2009;Tuncay 2007), experience lesser psychological stress (Carmody et al 2008), experience lower levels of suicidal ideation (Rasic et al 2011), and provide a sense of hope in extremely hopeless situations (Rasic et al 2011). The findings of the current study are consistent with those who found that individuals who have a close relationship with a higher power reported less symptoms of anxiety and depression.…”
Section: Discussionsupporting
confidence: 86%
“…Spirituality can alleviate physical and psychological problems and even social problems (Luquis et al 2012). Spirituality can provide a sense of hope in extremely hopeless situations, increase a sense of intimacy in individuals, be a source of comfort and relief from stress, provide meaning and a useful goal in life, and help in finding effective solutions to problems (Cotton et al 2009). Psychologists believe that spirituality plays an important role in generating a positive coping style against stressful life events (Abdollahi and Talib 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The PedsQL TM 4.0 Generic Core Scales has been utilized in pediatric psychiatric disorders, demonstrating significant impairments in HRQOL (Storch et al 2007; and significant correlations with the Child Behavior Checklist (Bastiaansen et al 2004a;Felder-Puig et al 2008) and measures of emotional distress including the Children's Depression Inventory (Cotton et al 2009;Varni et al 1999) and Social Phobia and Anxiety Inventory for Children and Short Mood and Feeling Questionnaire (Reinfjell et al 2008). One study (Bastiaansen et al 2004b) that utilized the PedsQL TM 4.0 Generic Core Scales to assess the HRQOL of children with psychiatric disorders included a small sample (n = 28) of children with Pervasive Developmental Disorders.…”
Section: Introductionmentioning
confidence: 99%